Arabica Coffee Farming and Marketing Chain Analysis in Manggarai and EastManggarai Districts - Dhiany. Faila Sophia Hartatri; Bernard de Rosari (Coffee and Cocoa Research Journal, 2011)
Arabica coffee has a unique flavour and very potential market. The purpose of this study was to analyse Arabica coffee farming and to investigate its performance of marketing chains in Manggarai and East Manggarai Districts, Flores, East Nusa Tenggara Province. This research was conducted in 2008-2010 by interviewing coffee farmers and coffee buyers; using open and close questions. The number of respondents were 100 people in each district. The result showed that land holding per household farmer in Manggarai and East Manggarai were 0.84 ha and 0.92 ha, respectively. Farmers in both districts were within the range of productive age, the farmers who were members of farmer groups in both study sites was £ 50%. Arabica coffee cultivation was still done in a traditional way. Fertilizing and controlling of pest and diseases had not been carried out inten sively. Arabica coffee farming in both district was feasible. BCR, NPV and IRR values in Manggarai were 4.2, Rp8,530,105, and 70.76% respectively, while BCR, NPV, and IRR value in East Manggarai district were 8.1, Rp2,465,833, and 27%, respectively. BEP production and coffee price in Manggarai were 94.2 kg/ha/th and Rp15,913/kg respectively, whereas BEP production and coffee price in East Manggarai were 78,2 kg/ha/th and Rp10,134/kg, respectively. In general, farmers sold their coffee in green bean form. In general, the marketing chains of Arabica coffee in both districts was farmer – collector - trader - exporter.